2005
DOI: 10.1080/10915810500366765
|View full text |Cite
|
Sign up to set email alerts
|

Refining the Effects Observed in a Developmental Neurobehavioral Study of Ammonium Perchlorate Administered Orally in Drinking Water to Rats. I. Thyroid and Reproductive Effects

Abstract: A recent study further investigated the potential effects of maternal thyroid function and morphology on fetal development upon maternal exposure to ammonium perchlorate during gestation and lactation. Female Sprague-Dawley rats (25/group) were given continual access to 0 (carrier), 0.01, 0.1, 1.0, and 30.0 mg/kg-day perchlorate in drinking water beginning 2 weeks prior to cohabitation through lactation day 10. Maternal, fetal, and pup serum thyroid hormone (thyroid-stimulating hormone [TSH], triiodo thyronine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 25 publications
2
21
1
Order By: Relevance
“…In another study with volunteers given perchlorate in drinking water the administered dose was negatively correlated with thyroidal iodide uptake but even a 70% decrease in iodide transport did not result in altered t4 levels (Greer et al, 2002;Strawson et al, 2004). the relatively low developmental toxicity of perchlorate is supported by animal studies showing that pregnant rats and rabbits exposed to a perchlorate dose as high as 30 mg/kg bw/ day do not give birth to offspring with signs of developmental toxicity and changes in thyroid hormone levels were seen as adaptive and reversible (York et al, 2003(York et al, , 2005.…”
Section: Discussionmentioning
confidence: 64%
“…In another study with volunteers given perchlorate in drinking water the administered dose was negatively correlated with thyroidal iodide uptake but even a 70% decrease in iodide transport did not result in altered t4 levels (Greer et al, 2002;Strawson et al, 2004). the relatively low developmental toxicity of perchlorate is supported by animal studies showing that pregnant rats and rabbits exposed to a perchlorate dose as high as 30 mg/kg bw/ day do not give birth to offspring with signs of developmental toxicity and changes in thyroid hormone levels were seen as adaptive and reversible (York et al, 2003(York et al, , 2005.…”
Section: Discussionmentioning
confidence: 64%
“…A recent study reported that perchlorate exposure in women with low iodide intake caused changes in TH levels [19]. In experimental studies using rats, perchlorate exposure decreased serum levels of T 4 and T 3 and increased thyroid stimulating hormone (TSH) levels [27,28]. High doses of perchlorate in rodents during fetal development resulted in permanent detriment to the brain function of the pup [29].…”
Section: Introductionmentioning
confidence: 99%
“…The pathological grading system used was that proposed by Kaplan-Lefko, which considers several criteria such as epithelial cytoarchitecture and the presence of mitosis, apoptosis and inflammation (28). The percentages of normal and pathological acini were registered.…”
Section: Histopathology and Immunohistochemistrymentioning
confidence: 99%
“…The TRAMP mice were obtained from The Jackson Laboratory (Bar Harbor, ME, USA 4 -inhibits >80% of iodide uptake in thyroid gland (positive control) (28). Thyroid, prostate and liver were collected, and the radiolabel was measured in counts per minute (cpm) in a γ-counter (Packard, Palo Alto, CA, USA).…”
Section: Transgenic Animalsmentioning
confidence: 99%